PENINGKATAN EKONOMI PETERNAK BABI DI KELURAHAN SIKUMANA MELALUI PELATIHAN PENGENCERAN SEMEN DAN INSEMINASI BUATAN - Yustinus Oswin Primajuni Wuhan; Yohanes Timbun Raja Mangihut Ronael Simarmata; Arjuna Purba (Universitas Nusa Cendana, 2026)
Enhancing community welfare through inclusive economic growth is one of the key targets of the eighth Sustainable Development Goal (SDG). In this context, strengthening small-scale livestock farming plays a crucial role in improving household income and ensuring food security. East Nusa Tenggara (NTT), particularly Sikumana Village in Kupang City, has significant potential in pig farming; however, productivity remains low due to limited access to superior breeding stock and inadequate knowledge of modern reproductive technologies. The main problems faced by local farmers include poor genetic quality caused by inbreeding, reduced litter size, high post-parturition mortality, and low market value of piglets. This community service program aimed to improve the knowledge and skills of pig farmers in Sikumana Village through training in semen dilution and artificial insemination (AI) techniques. The activities included awareness sessions, hands-on training in semen dilution and packaging, practical exercises in AI procedures, and workshops on farm management and financial administration. Evaluation was carried out using participatory observation and group discussions to assess improvements in farmers’ understanding and technical abilities. The results showed a marked increase in farmers’ knowledge and technical competence in semen dilution, microscopic evaluation of sperm quality, and independent application of AI in their herds. The donation of basic laboratory and insemination equipment further supported the program’s sustainability. The immediate impacts included improved breeding efficiency, reduced inbreeding risk, and the potential for higher income through better reproductive performance. Collaboration between the university and local farmer groups proved effective in applying appropriate technology to support sustainable local economic development.